Perancangan Buen Art Center di Penajam Paser Utara dengan Pendekatan Ikonik Pada Bentuk Bangunan - Nurzakiyah, Nurzakiyah; Ramadhani, Suci; Ratniarsih, Ika (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2024)
The Penajam area is a district located in Penajam Paser Utara, East Kalimantan with 110,240 inhabitants and a total area of 3,333.06 km² in 2002. As long as North Penajam Paser was established, there was not a single Art Center building, and many festivals were often held in Penajam such as the Nondoi Festival, Belian traditional festival, Serambi Nusantara. So this design aims to create an Arts Center that will accommodate artistic activities in North Penajam Paser. The Buen Art Center was planned using an architectural approach that designs a building using data and social habits of a place, and something that is associated with an "icon" or "Vocal Point" in the form of a building. This art center building is located on Coastal Road Km.9 Nipah-Nipah, Penajam District, North Penajam Paser Regency, East Kalimantan Province. In applying the shape of this building, the concept of shape is used by applying a shape that resembles a ship when seen from the front view and the building will look like sea waves when seen from the right side view and also the left side view. From the results of this design, it is hoped that the results of the Buen Art Center design can become a place that can accommodate art activities and all activities connected to art, art activities and all art activities as well as preserving and introducing people inside and outside the region about North Penajam Paser art.